KHOO KAY KIM, PROFESSOR OF MALAYSIAN HISTORY: A BIOBIBLIOMETRIC STUDY - Tiew, Wai Sin (Malaysian Journal of Library and Information Science, 1999)
Presents an analysis of the publication productivity, authorship pattern, channels of communication, journal preference and language preference of Professor Dato’ Khoo Kay Kim, Professor of Malaysian History in the University of Malaya, Kuala Lumpur. The results of this biobibliometric study indicate that he can be a role model for future Malaysian historians to emulate his various achievements especially in the field of history education